Гимназиите во османлиска Македонија - Минов, Никола (Филозофски факултет, Скопје, 2017)
The text offers a comparative analysis of the role and the objectives of four high schools in Ottoman Macedonia: the Serbian Boys’ Gymnasium in Skopje; the Greek Boys’ Gymnasium in Bitola; the Romanian Boys’ Lyceum in Bitola; and the Bulgarian Boys’ Gymnasium in Thessaloniki. The final conclusion – that all these educational institutions, despite their conflicting interests, followed the same modus operandi – is based on the answers of the following questions: Who financed these high schools? What was the internal structure of each of the four schools (curriculum; language of instruction; major subjects; schoolbooks)? What kind of qualifications did the students acquire after graduation? What was the role of the boarding schools? What was the ethnic origin and social class of the students, as well as the origin and the personal background of the teaching staff and the school directors?